A Domain-Specific approach for Programming Wireless Body Sensor Network Systems - Gravina, Raffaele; Palopoli, Luigi; Fortino, Giancarlo (My University, 2011)
The progress of science and medicine during the last years has contributed to signi cantly increase the average life expectancy. The increase of elderly population will have a large impact especially on the health care system. Furthermore, especially in more developed countries, there is an always growing interest in maintaining, and improving the quality of life. Wireless Body Sensor Networks (BSNs) can contribute to improve the quality of health care services. BSNs involve wireless wearable physiological sensors applied to the human body for strictly medical and non medical purposes. They can enhance many human-centered application domains such as e-Health, sport and wellness, and even social applications such as physical/ virtual social interactions. However, there are still open issues that limit their wide di usion in real life; primarily, the programming complexity of these systems, due to lack of high-level software abstractions, and to hardware constraints of wearable devices. In contrast to low-level programming and general-purpose middleware, domain-speci c frameworks are an emerging programming paradigm designed to ful ll the lack of suitable BSN programming support. With this aim, this thesis proposes a novel domain-speci c approach for programming signal-processing intensive BSN applications. The de nition of this approach resulted in a domain-speci c programming framework named SPINE (Signal Processing in Node Environment) which is one important contribution of this thesis, along with other interesting contributions derived from enhancements and variants to the main proposal. Additionally, to provide validation and performance evaluation of the proposed approach, a number of BSN applications (including human activity monitoring, physical energy expenditure estimation, emotional stress detection, and step-counting) have been developed atop SPINE. These research prototypes showed the e ectiveness and e ciency of the proposed approach and improved their respective state-of-the-art. Finally, a Platform-Based Design (PBD) methodology, which is widely adopted for the design of traditional embedded systems, is proposed for the design of BSN systems.
Dottorato di Ricerca in Ingegneria dei Sistemi e Informatica XXIV Ciclo, a.a. 2011
Keywords: Reti wireless; Sensori